2022
DOI: 10.1002/jbt.23048
|View full text |Cite
|
Sign up to set email alerts
|

LINC01140 inhibits nonsmall cell lung cancer progression and cisplatin resistance through the miR‐4742‐5p/TACC1 axis

Abstract: Recent studies show that lncRNAs participate in drug resistance and nonsmall cell lung cancer (NSCLC) progression. This study aimed to study the roles and mechanisms of long intergenic nonprotein coding RNA 01140 (LINC01140) in regulating NSCLC progression and drug resistance. Real‐time quantitative polymerase chain reaction and western blot analysis were used to detect LINC01140, miR‐4742‐5p, and transforming acidic coiled‐coil 1 (TACC1) expression in NSCLC cells. The interaction between two molecules was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…TACC1 has the ability to transform fibroblasts and, as evidenced by current research, positively regulates the Ras and PI3K signaling pathways to promote transformation and mammary carcinogenesis. The progression of non-small cell lung cancer is halted by the microRNA miR-4742-5p, which inhibits TACC1 expression [123].…”
Section: Targeting Pm Proteomic Profilementioning
confidence: 99%
“…TACC1 has the ability to transform fibroblasts and, as evidenced by current research, positively regulates the Ras and PI3K signaling pathways to promote transformation and mammary carcinogenesis. The progression of non-small cell lung cancer is halted by the microRNA miR-4742-5p, which inhibits TACC1 expression [123].…”
Section: Targeting Pm Proteomic Profilementioning
confidence: 99%
“…LINC01140 is a potential regulator of cancer drive or containment in different tumors. LINC01140 inhibits the progression of lung cancer [ 12 ] and sarcomas [ 13 ], whereas it promotes bladder cancer. Li et al have analyzed the cBioPortal database and reported that LINC01140 expression is significantly reduced in the tumor samples from BC patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%